The Concept of Aswaja in the Thought of K. Abul Fadlol As-Senori (1916-1991 AD) and its Relationship with Aswaja in the Thought of KH. Hashim Ash`ari - Faizin, Nur; Basid, Abdul; Ramadhan, Mochammad Rizal; Aliyyah, Dza Himmatin; Nasih, Ahmad Munjin; Marjuni, Kamaluddin Nurdin (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
The concept of Ahlu sunnah wal jamaah (Aswaja) remains a subject of frequent debate. This article endeavors to provide a comprehensive exploration of the Aswaja concept through the perspective of the archipelago scholar, K. Abu Fadlol As-Senori, a disciple of KH. Hashim Ash`ari, the founder of the Nahdlatul Ulama. This article also strives to establish a connection between the concept of Aswaja as it is found and the Aswaja concept of KH. Hashim Ash`ari. This research is a descriptive-qualitative study. This study revealed that Aswaja, as defined by K. Abul Fadlol, encompasses four distinct groups: (1) the Muhadditsin, (2) the Sufiyyah (3) the Ash'ariyah and (4) Maturidiyah. As a student of KH. Hashim Ash`ari, the Aswaja concept of K. Abul Fadlol has a very big aspect of similarity. The concept of Aswaja from both becomes the foundation for building moderation in religion. Both also reject hardline Islamists who claim to be Aswaja